Long term effects of bosentan treatment in adult patients with pulmonary arterial hypertension related to congenital heart disease (Eisenmenger physiology): safety, tolerability, clinical, and haemodynamic effect. Issue 5 (29th November 2006) - D'Alto, M; Vizza, C D; Romeo, E; Badagliacca, R; Santoro, G; Poscia, R; Sarubbi, B; Mancone, M; Argiento, P; Ferrante, F; Russo, M G; Fedele, F; et al.
Abstract : Background: Oral bosentan is an established treatment for pulmonary arterial hypertension (PAH). Objective: To evaluate safety, tolerability, and clinical and haemodynamic effects of bosentan in patients with PAH related to congenital heart disease (CHD). Patients: 22 patients with CHD related PAH (8 men, 14 women, mean (SD) age 38 (10) years) were treated with oral bosentan (62.5 mg×2/day for the first 4 weeks and then 125 mg×2/day). Main outcome measures: Clinical status, liver enzymes, World Health Organisation (WHO) functional class, resting oxygen saturations and 6-min walk test (6MWT) were assessed at baseline and at 1, 3, 6, and 12 months. Haemodynamic evaluation with cardiac catheterisation was performed at baseline and at 12 month follow-up. Results: 12 patients had ventricular septal defect, 5 atrioventricular canal, 4 single ventricle, and 1 atrial septal defect. All patients tolerated bosentan well. No major side effects were seen. After a year of treatment, an improvement was seen in WHO functional class (2.5 (0.7) v 3.1 (0.7); p<0.05), oxygen saturation at rest (87 (6%) v 81 (9); p<0.001), heart rate at rest (81 (10) v 87 (14) bpm; p<0.05), distance travelled in the 6MWT (394 (73) v 320 (108) m; p<0.001), oxygen saturation at the end of the 6MWT (71 (14) v 63 (17%); p<0.05), Borg index (5.3 (1.8) v 6.5 (1.3); p<0.001), pulmonary vascular resistances index (14 (9) v 22 (12) WU m 2 ; p<0.001), systemic vascular resistances index (23 (11) v 27 (10) WU.m 2 ; p<0.01), pulmonary vascular resistances index/systemic vascular resistances index (0.6 (0.5) v 0.9 (0.6); p<0.05); pulmonary (4.0 (1.3) v 2.8 (0.9) l/min/m2; p<0.001) and systemic cardiac output (4.2 (1.4) v 3.4 (1.1) l/min/m2; p<0.05). Conclusions: Bosentan was safe and well tolerated in adults with CHD related PAH during 12 months of treatment. Clinical status, exercise tolerance, and pulmonary haemodynamics improved considerably.